Designing central heating and cooling systems acknowledging simultaneous heat loads in Audytor SET software - Strzeszewski, Michał; Wereszczyński, Piotr (Instal, 2021)
The article discusses the proposed method of acknowledging the simultaneous occurrences of heat loads when designing central heating and cooling systems. The partial heat load coefficient has been defined. The results of exemplary calculations for a multi-family building are also discussed.
Keywords: HVAC; Audytor HL; Audytor SET; partial heat loads